ChemInform Abstract: Diastereoselective Synthesis of Highly Functionalized Quinolizines via a Pyridine‐Based Three‐Component Reaction and a DFT Investigation on the Reaction Mechanism. Issue 25 (24th June 2014) - Esmaeili, Abbas Ali; Zarifi, Farzaneh; Moradi, Abbas; Izadyar, Mohammad; Fakhari, Ali Reza
Abstract This novel, one‐pot, three‐component reaction affords quinolizine derivatives via 1, 4‐dipolar cycloaddition without using any catalyst or activation.